Urinary fistulas after partial nephrectomy in renal cell carcinoma - B. G. Guliev (Вестник урологии)
Urinary fistulas after partial nephrectomy are rare complications of this operation. There are various reasons for their development, prevention and treatment. This review analyzes the results of the cases' prevalence of urine leakage after partial nephrectomy with various approaches, occurrence's predictors of urinary fistulas, possible ways of their intraoperative prevention and treatment methods. The obtained data show that the size of tumors, their endophytic nature and proximity to the kidney pelvicalyceal system, as well as suturing of its defect, can be predictors of the development of urinary fistulas (UFs). Some authors point to the influence of long ischemia time and high blood loss on the occurrence of UFs. The main method of treating UFs is ureteral stenting or percutaneous drainage of the kidney pelvicalyceal system. For long-term persistent UFs, the method of choice can be simultaneous introduction of 2 stents, retrograde or percutaneous injection of fibrin glue, percutaneous cryoablation of the UFs.